2022
DOI: 10.22610/jebs.v14i2(j).3301
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Workforce Diversity on Organizational Performance: A Review

Abstract: The paper aims to review the literature on the effect of workforce diversity including, gender, culture/race, age, and ethnicity, on firm performance. Many empirical papers have been reviewed in which different statistical models have been applied to data of multiple types of organizations across the regions and continents to find the association between the selected variables. The review methodology is selected to survey the literature on the impact of workforce diversity on organizational performance between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…The performance of organizations is significantly enhanced by a diverse workforce, resulting in increased creativity, problem-solving, communication, and productivity, compared to a homogenous one. A review investigation by Rafaqat et al, (2022) found that the Performance of organizations is strongly correlated with worker diversity. Furthermore, a diverse workforce can be productive if it is balanced well.…”
Section: Diversity In the Workplacementioning
confidence: 99%
“…The performance of organizations is significantly enhanced by a diverse workforce, resulting in increased creativity, problem-solving, communication, and productivity, compared to a homogenous one. A review investigation by Rafaqat et al, (2022) found that the Performance of organizations is strongly correlated with worker diversity. Furthermore, a diverse workforce can be productive if it is balanced well.…”
Section: Diversity In the Workplacementioning
confidence: 99%
“…Our research has relevance for the growing literature on the impact of diversity and inclusion policies on workplace performance. Rafaqat et al (2022) reviews the literature of the last two decades and finds that workforce diversity is significantly related to organizational performance. Studies that find positive impacts of diversity are more prevalent than those that find negative impacts.…”
Section: Public Service Diversity Incentives and Performancementioning
confidence: 99%
“…The aspects of diversity are multifaceted, including not only age, gender, and cultural background but also dimensions like religious beliefs, mental and physical abilities, and sexual orientation. A growing body of research indicates a strong positive relationship between a diverse workforce and multiple aspects of organizational performance, such as innovation and financial growth (Ehilebo et al, 2022;Rafaqat et al, 2022). However, the contexts and methods in which these studies were conducted limit their universal applicability.…”
Section: Introductionmentioning
confidence: 99%